Regulation Vs Legislation of Nursing Practice - Farid Rivai, Ahmad (Ann Publisher, 2024)
Parallel operations take place in the legislative and regulatory systems. The procedures are distinct, but they are both equally powerful and public. Draft legislation (RUU) and passed laws (UU) are considered legislation. Enforcement of the law can be reasonable when it is regulated. The regulation is made in-depth and establishes the practical application of the legislation if it is written generally. A technique for gathering library data is employed, whereby the research subject is tracked down using a range of information from the literature. Bibliographic annotation analysis is the type of data analysis employed; it is a concise synopsis or crucial overview of the reading process of an article. Based on the findings of this study, regulations about the health profession are necessary to safeguard public safety interests by serving as a barrier to entry. The legal aspects of nursing practice are uncertain due to the rapid changes in regulations governing nursing registration and practice; therefore, nurses are seeking legislative stability. The 2014 Nursing Law number 38 of 2014 was released by the government. Due to their ability to control their fate and obtain the desired legal protection, Indonesian nurses are now considered respected professionals thanks to this legislation. Moreover, after nearly ten years, the Nursing Law was repealed, and law number 17 of 2023 concerning OBL Health (omnibus law) took its place. Adaptability is critical in a time of fast change, and the conclusion is drawn. There are numerous opportunities for politically astute nurses nowadays to influence public policy. Nurses can successfully manage the changeable environment if they are familiar with the regulatory process.